Minimisation of the viral contamination risk of heterologous immunoglobulins in the context of the requirements of the State Pharmacopoeia of the Russian Federation - V. V. Mashin; A. N. Sergeev; N. N. Martynova; T. V. Antipina; E. I. Sakanyan; V. V. Kataeva; N. V. Zagidullin (Биопрепараты: Профилактика, диагностика, лечение, 2022)
To ensure the safety and to secure the approval of injectable medicinal products based on antigen-specific immunoglobulins of animal origin, it is necessary to exclude their contamination with adventitious human pathogens. Ensuring the viral safety of heterologous immunoglobulins presents a major challenge, because the State Pharmacopoeia of the Russian Federation, 14 edition, lacks production stage-specific viral safety requirements for such medicinal products. The aim of the study was to analyse the requirements set forth in general and individual monographs of the State Pharmacopoeia of the Russian Federation, the European Pharmacopoeia, (10th edition), the British Pharmacopoeia (2019), the United States Pharmacopoeia (USP 43–NF 38), the Japanese Pharmacopoeia (17th edition), as well as the recommendations of the European Medicines Agency and the World Health Organisation concerning the viral safety of medicinal products for human use based on heterologous antigen-specific immunoglobulins. The authors analysed regulatory requirements for the following: serum/plasma-producing animals; immunisation antigens for the animals; quarantine of the animals; viral contamination tests for immune animal serum/plasma pools; model viruses to validate viral inactivation/removal processes at different stages of vaccine production; viral load reduction at each inactivation/ removal step; testing of materials obtained at critical production stages. The authors drafted sections for quality standards on production stage-specific measures to minimise the viral contamination risk of medicinal products for human use based on heterologous immunoglobulins, which they proposed for inclusion to the State Pharmacopoeia of the Russian Federation.